O paradoxo de Hegel: liberdade e escravidão nas colônias (Revista Eletrônica Estudos Hegelianos, 2019)
Susan Buck-Morss in Hegel and Haiti defends that Hegel, unlike most modern philosophers, considered slavery in the colonies – notably the Haitian revolution – to develop his own philosophy, particularly Phenomenology of Spirit. Hegel conceived a theory of freedom with insight uncommon at the time. Buck-Morss understands that this can be used as the foundation to review, in contemporary terms, the idea of a universal history without exclusivity and Eurocentricity. In light of a decolonial perspective, the theories presented by the philosopher on universality cannot be supported and it is possible to expose the real problems that Hegelianism seeks to solve surrounding emancipation and to whom, in particular, it is destined when he learned of the Haitian Revolution. The problematization of such theories sheds new light on certain decisive aspects of the subaltern, which we insist on analyzing using the tradition of philosophical thinking in reconsidering categories that do not help us to study or offer opinions in current times.